2021
DOI: 10.1016/j.jtumed.2020.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the gender diversity and affiliation trends of the authors for two orthopaedics journals from the Arab world

Abstract: Objectives Authorship trends, female authors' contributions, and the collaboration among institutions have been a concern in the medical field. This study primarily aims to report and compare the number of authors per article and the prevalence of female authors by comparing two orthopaedics journals from the Arab world. The secondary objective of this study is to evaluate the characteristics of the authors' affiliations and the pattern in institutions' collaborations and contributions to the publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…25,26 A study by Khalifa et al determined the prevalence of female authorship of 2 orthopaedic journals in Saudi Arabia and Egypt to be ~14.0% and 0.3%, respectively. 27 Contrarily, Portugal has passed legislation mandating a minimum 40% inclusion rate for men and women candidates for administrative boards of higher-education institutions, a change which some experts say may have contributed to women accounting for nearly half of all authors in their nation. 28 When considering the lag in recognition of female orthopaedic surgeons some proposed reasons include the low percentage of practicing female orthopaedic surgeons, decreased number of female orthopaedic surgeons/mentors in high-ranking positions, perspective that the field is not friendly to females and/or conducive to females looking for a balanced work-life schedule and family planning, lack of exposure to orthopaedic principles and foundations in medical school, expensive pathway to becoming an orthopaedic surgeon, and greater fit of other medical specialties.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 A study by Khalifa et al determined the prevalence of female authorship of 2 orthopaedic journals in Saudi Arabia and Egypt to be ~14.0% and 0.3%, respectively. 27 Contrarily, Portugal has passed legislation mandating a minimum 40% inclusion rate for men and women candidates for administrative boards of higher-education institutions, a change which some experts say may have contributed to women accounting for nearly half of all authors in their nation. 28 When considering the lag in recognition of female orthopaedic surgeons some proposed reasons include the low percentage of practicing female orthopaedic surgeons, decreased number of female orthopaedic surgeons/mentors in high-ranking positions, perspective that the field is not friendly to females and/or conducive to females looking for a balanced work-life schedule and family planning, lack of exposure to orthopaedic principles and foundations in medical school, expensive pathway to becoming an orthopaedic surgeon, and greater fit of other medical specialties.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these authors observed that Canadian women orthopaedists are underrepresented in terms of numbers, positions, and academic productivity. In another cross-sectional study, Khalifa et al [ 22 ] compared the number of authors per article and the prevalence of women authors in two orthopaedic journals from the Arab world: the Archives of the Egyptian Orthopaedic Journal (EOJ) and the Journal of Musculoskeletal Surgery and Research (JMSR). These authors reviewed all articles published prior to July 2020 and found that the prevalence of women authors in the JMSR was significantly higher than in the EOJ (14.2% versus 0.3%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…These findings shed light on the need for institutional support for more active participation in scientific research and publication by women physicians, starting early in their education and specialty training. It is widely recognized that being up-to-date with scientific advancements and actively engaging in academic activities are crucial factors for professional advancement in various orthopaedic disciplines [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, compared with North America, Africa, and the Middle East have a greater proportion of single-authored articles. 35,36 Thus, in countries where research productivity is less closely tied to career advancement, fewer people may feel the pressure to obtain publications. Consequently, supply is more closely matched to demand.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas in the United Kingdom and Ireland, the publication requirement for entry into surgical training has reduced 34 —a maximum score is achieved after publication of a single first-authored original research article. Furthermore, compared with North America, Africa, and the Middle East have a greater proportion of single-authored articles 35,36 . Thus, in countries where research productivity is less closely tied to career advancement, fewer people may feel the pressure to obtain publications.…”
Section: Discussionmentioning
confidence: 99%